Lithraea caustic (Litre) Extract Promotes an Antitumor Response Against B16 Melanoma - Robles-Planells, Claudia; Michelson, Sofia A.; Mena, Javier; Escrig, Daniela; Rojas, Juan L.; Sanchez-Guerrero, Giselle; Hernández, Ronny; Barrera-Avalos, Carlos; Rojo, Leonel E.; Sauma, Daniela; Kalergis, Alexis M.; Imarai, Mónica; et al. (Frontiers in Pharmacology, 2019)
Melanoma immunotherapy, specifically the auto transplant of dendritic cells charged with tumors antigens, has shown promising results in clinical trials. The positive clinical effects of this therapy have been associated to increased Th17 response and Delayed-Type Hypersensitivity (DHT) against to tumor antigens. Some synthetic compounds, such as Diphenylcyclopropenone (DPCP), are capable of triggering a DTH response in cutaneous malignancies and also to induce clinically relevant effects against melanoma. In this work, we evaluated LExT, a standardized extract of a Chilean stinging plant, Lithraea caustic (Litre). As Litre plant is known to induce DHT, we used a murine B16 melanoma model to compare the topical and intratumor efficacy of LExT with synthetic DTH-inducers (DPCP and DNCB). LExt contained mainly long chain catechols and sesquiterpenes. The intratumor injection of LExT induced a significant delay in tumor growth, similarly topical treatment of an established tumor with 0.1% LExT ointment induced a growth delay and even tumor regression in 15% of treated animals. No significant changes were observed on the T cell populations associated to LExT treatment, and neither 2,4-Dinitrochlorobenzene (DNCB) nor DPCP were capable to induce none of the LExT-induced antitumoral effects. Interestingly, our results indicate that LExT induces an antitumor response against melanoma in a mouse model and could bring a new –and affordable- treatment for melanoma in humans.